EKSISTENSI MUSEUM ADITYAWARMAN DAN DAMPAKNYA TERHADAP KEBUTUHAN INFORMASI PENGUNJUNG - Pratama, Harby; Marlini, Marlini (Departemen Informasi Perpustakaan dan Kearasipan, 2023)
This research aims to describe the existence of the Adityawarman Museum and its impact on visitors' information needs. This research uses quantitative descriptive methods. The research population was 50,540 people with a sample of 100 people. The sampling technique uses an incidental sampling technique. Data analysis in this research was carried out by examination, then tabulation and data processing were carried out by calculating using the mean formula to calculate the average per statement item, as well as calculating the grand mean to calculate the total average of each indicator. The research results show that the existence of the Adityawarman Museum and its impact on visitors' information needs is good.